2010
DOI: 10.1002/ps.1961
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of trifloxystrobin and tebuconazole on grapes under semi‐arid tropical climatic conditions

Abstract: Residue levels of both trifloxystrobin and tebuconazole were below MRLs when grapes were harvested 30 days after the last of four applications of 175 g product ha(-1) (trifloxystrobin 44 g AI ha(-1), tebuconazole 88 g AI ha(-1)) under the semi-arid tropical climatic conditions of India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 4 publications
4
10
0
Order By: Relevance
“…Soil samples collected after 15 days did not reveal the presence of tebuconazole at the determination limit of 0.05 mg kg -1 (Table 3). On grapes, the average initial deposit of tebuconazole were estimated to be 0.53 and 1.22 mg kg -1 , following four application of Nativo 75 WG (trifloxystrobin 250+ tebuconazole 500 g mg -1 ) at 175 and 350 g ha -1 , respectively which were in conformity with results of the present study [10]. Similarly, initial deposits of tebuconazole on chilli were found to be 0.95 and 1.88 mg kg -1 , respectively, following two application of Nativo 75WG (trifloxystrobin 25%+ tebuconazole 50%) @ 250 and 500 g ha -1 , which dissipated with half life values of 1.37 and 1.41 days, respectively [13].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Soil samples collected after 15 days did not reveal the presence of tebuconazole at the determination limit of 0.05 mg kg -1 (Table 3). On grapes, the average initial deposit of tebuconazole were estimated to be 0.53 and 1.22 mg kg -1 , following four application of Nativo 75 WG (trifloxystrobin 250+ tebuconazole 500 g mg -1 ) at 175 and 350 g ha -1 , respectively which were in conformity with results of the present study [10]. Similarly, initial deposits of tebuconazole on chilli were found to be 0.95 and 1.88 mg kg -1 , respectively, following two application of Nativo 75WG (trifloxystrobin 25%+ tebuconazole 50%) @ 250 and 500 g ha -1 , which dissipated with half life values of 1.37 and 1.41 days, respectively [13].…”
Section: Resultssupporting
confidence: 91%
“…These results were in agreement with findings of earlier workers [13], who reported initial deposits of trifloxystrobin on chilli to be 0.31 and 0.59 mg kg -1 , following two applications of Nativo 75 WG @ 250 and 500 g ha -1 , and residues dissipated with half life of 1.81 and 1.58 days, respectively. Similarly, 0.30 and 0.87 mg kg -1 initial deposits of trifloxystrobin were reported on grapes at single (175 g ha -1 )and double dose (350 g ha -1 ) of Nativo 75 WG, respectively [10]. However, in another study the initial deposits of 7.76 and 15.53 mg kg -1 were reported, following the application of trifloxystrobin 25% + tebuconazole 50% (Nativo 75 WG) @ 43.75 and 87.5 g a.i.ha -1 with respect to trifloxystrobin on grapes, respectively [11].…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…So, it might be stated that Tebuconazole may not pose any residual toxicity problem in paddy and groundnut. Similar observations were also reported earlier about the safety issue of Tebuconazole [11][12][13][14][15][16]. Based on these findings, he use of Tebuconazole 25.9% EC in paddy and groundt nut in West Bengal may be advocated for the control of fungal diseases in paddy and groundnut.…”
Section: Residues Of Tebuconazole In Harvest Samplessupporting
confidence: 85%
“…Jyot et al (2010) determined a DT 50 value of less than 5 days and no detectable residues at 34 DAA when a mixture of trifloxystrobin + tebuconazole was applied to grape berries. In contrast, Mohapatra et al (2010) found tebuconazole residues in grape berries at 30 DAA and a DT 50 of approximately 20 days after the same mixture was applied. In this study.…”
Section: Discussionmentioning
confidence: 77%